(untitled) ("Journal "U". Economy. Management. Finance.", 2019)
The article is devoted to the analysis of investments into the fixed capital of the Russian Federation. The article reveals the concept and essence of investing fixed capital. The dynamics of investing in the fixed capital of the Russian Federation is considered. The main directions for attracting investments are given.